INCORPORATION OF ISOACIDS, OIL, NPN AND PROTEIN IN THE RATION OF SHEEP AND THEIR EFFECTS ON PROTEASE AND AMYLASE IN THE RUMEN FLUID - Moharrery, A. (Emirates Journal of Food and Agriculture, 2017)
Please see the scanned pdf version in full text